The Comparative Analysis of Cost of Production Using Full Costing, Variable Costing, and Activity-Based Costing Methods in MSMEs of Tanjungpinang City - Aditia Ayu Rahma Nabila (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2026)
Culinary sector MSMEs continue to face challenges in determining accurate Cost of Production (COP), which often leads to pricing errors. This study aims to analyze and compare the calculation of COP using Variable Costing, Full Costing, and Activity-Based Costing (ABC) methods in a Sempol MSME located in Tanjungpinang. A descriptive quantitative approach was employed, with data collected through observation and interviews related to production costs and production volume. The results indicate that the COP of sempol was Rp541,66 per stick using the Variable Costing method and Rp609,86 per stick using the Full Costing method, while the COP of sausages was Rp658,39 and Rp692,49 per stick, respectively. The ABC method produced lower COP values, namely Rp105,76 per stick for sempol and Rp30,44 per stick for sausages, as costs were allocated based on production activities. This study concludes that different costing methods generate different cost information; therefore, the selection of an appropriate COP method should be aligned with the analytical objectives and cost management needs of MSMEs.